Factors associated with the consumption of fruits and vegetables by schoolchildren: a comparative analysis between 2007 and 2012 - SOAR, Claudia; Garcia GABRIEL, Cristine; das NEVES, Janaina; BRICARELLO, Liliana Paula; Lennon MACHADO, Mick; de Assis Guedes de VASCONCELOS, Francisco (Revista de Nutrição, 2023)
Objective Perform comparative analysis of adequate consumption of fruits and vegetables and their associated factors in schoolchildren. Methods Probabilistic samples representative of students of both sexes, 7 to 14 years old, from public and private schools in Florianópolis, SC were investigated in cross-sectional studies in 2007 (n=2,836) and 2012 (n=2,506). The exposure variables were: sex, age, family income per capita, mother’s education and school system. The outcome variable (fruit and vegetable consumption) was collected using the third validated version of the previous day’s food questionnaire. Using the Chi-Square test, exposure variables with a p-value <0.20 were eligible for analysis using crude and adjusted multiple logistic regression models. Exposure variables with p<0.05 were considered to be associated with the consumption of fruits and vegetables. Results There were no significant differences in the adequate consumption between 2007 and 2012. While in 2007 the per capita family income was the only exposure variable associated, in 2012 only a mother with complete higher education was a protective factor for the adequate consumption of fruits and vegetables. Conclusion Despite governmental strategies to stimulate the consumption of fruits and vegetables in Brazil, their results are still not perceptible, requiring more time for an evaluation of effectiveness.